2021
DOI: 10.1007/s00383-020-04827-5
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analyses in paediatric surgery are often fragile: implications and consequences

Abstract: Purpose Meta-analyses occupy the highest level of evidence and thereby guide clinical decision-making. Recently, randomised-controlled trials were evaluated for the robustness of their findings by calculating the fragility index. The fragility index is the number of events that needs to be added to one treatment arm until the statistical significance collapses. We, therefore, aimed to evaluate the robustness of paediatric surgical meta-analyses. Methods We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…Consistent results were observed by Schröder et al [5], depicting a median (Q1-Q3; range) FI of 5 (2-11; 1-50) among the meta-analyses related to pediatric surgery. The authors have very aptly discussed the rarity of the pediatric surgical ailments as the possible reason behind the low FI among these meta-analyses.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Consistent results were observed by Schröder et al [5], depicting a median (Q1-Q3; range) FI of 5 (2-11; 1-50) among the meta-analyses related to pediatric surgery. The authors have very aptly discussed the rarity of the pediatric surgical ailments as the possible reason behind the low FI among these meta-analyses.…”
Section: Discussionsupporting
confidence: 87%
“…Later, Atal et al demonstrated its application for meta-analyses of RCTs [4]. A recent study by Schröder et al [5] has shown its wider applicability and has supported its use for meta-analyses of observational studies also. Although the application of FI for meta-analyses of non-RCTs is a point of debate, the technical challenges of conducting good-quality RCTs in surgical specialties are even greater.…”
Section: Introductionmentioning
confidence: 99%
“…We truly appreciate that Saikia & Thakuria have found the time during this devastating pandemic to respond to our manuscript. It is a pleasure for us to respond to their comments to the editor in this issue of Paediatric Surgery International [ 1 ], which provides us with the valuable opportunity to point out some issues that may not have become clear enough in our initial contribution [ 2 ].…”
mentioning
confidence: 99%
“…The fragility index has been extended beyond this limitation before [ 8 10 ], and we have thus extended its applicability as well. Let us assume that we would have limited our analysis [ 2 ] to meta-analyses with these primary study properties: the underlying numbers would have possibly changed slightly, but it would not have changed our conclusion.…”
mentioning
confidence: 99%
“…To the editor, We are doing a few projects on fragility index of randomized controlled trials (RCTs) and meta-analyses. Therefore, we read the work by Arne Schröder and colleagues with great enthusiasm [1]. Ignacio Atal and colleagues described the fragility index of meta-analyses that include only RCTs reporting dichotomous outcome [2].…”
mentioning
confidence: 99%